Prospects of Silk Sericin Membranes Fabricated with Tyrosinase (Journal of Fiber Bioengineering and Informatics, 2015)
Biological enzyme is a kind of substance, which can catalyze specific reaction. In our work, sericin\rmembranes are prepared under the catalysis of tyrosinase, which promoting protein molecules crosslinking\rthrough tape casting method. Taking the water solubility of sericin membranes as the evaluation index,\rthe optimal preparation conditions are determined as follows: the dosage of tyrosinase 1000 U/g, the\rreaction temperature 45 \u00b0C, for 90 min, 2% glycerol and drying temperature at 45 \u00b0C. The results of\rinfrared spectra indicate that the structure of amide I is changed in crosslinked sericin membranes. The\rXPS results indicate the O atom content is increased in crosslinked sericin membrane. This verifies the\rcrosslinking of sericin protein by tyrosinase.
Keywords: Tyrosinase; Crosslinking; Sericin Membranes; Water Solubility